Improved Perturb & Observe Method by Particle Swarm Optimization Algorithm for Photovoltaic System - Bechouat, Mohcene; Feraga, Chams-Eddine; Attia, Mohammed El hadi; Sedraoui, Moussa (University of Eloued جامعة الوادي, 2018)
The Perturb and Observe (P&O) maximum power point tracking (MPPT) algorithm can be not robust where the rapid change in atmospheric conditions, especially it happened in irradiance, caused by the heuristic choice for the duty cycle perturbation and the duty cycle initialization. In this paper, it is shown how to integrate optimization method called Particle Swarm optimization (PSO) in P&O to choice the duty cycle perturbation and the first initialization condition based in maximizing power output. Using a DC-DC converter “Boost” associated with the photovoltaic panel; so working to get the maximum power that is mean, earn a good yield. The results of the simulation performed under the tool Simulink/Matlab shows the effectiveness of the integration PSO optimization method in P&O.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Photovoltaic systems, Boost, PWM, MPPT, P&O, PSO